Effects of cilostazol in kidney and skeletal striated muscle of Wistar rats submitted to acute ischemia and reperfusion of hind limbs - Moreira Neto,Antonio Augusto (2012)
PURPOSE: To investigate the effect of cilostazol, in kidney and skeletal muscle of rats submitted to acute ischemia and reperfusion. METHODS: Fourty three animals were randomized and divided into two groups. Group I received a solution of cilostazol (10 mg/Kg) and group II received saline solution 0.9% (SS) by orogastric tube after ligature of the abdominal aorta. After four hours of ischemia the animals were divided into four subgroups: group IA (Cilostazol): two hours of reperfusion. Group IIA (SS): two hours of reperfusion. Group IB (Cilostazol): six hours of reperfusion. Group IIB (SS) six hours of reperfusion. After reperfusion, a left nephrectomy was performed and removal of the muscles of the hind limb. The histological parameters were studied. In kidney cylinders of myoglobin, vacuolar degeneration and acute tubular necrosis. In muscle interstitial edema, inflammatory infiltrate, hypereosinophilia fiber, cariopicnose and necrosis. Apoptosis was assessed by immunohistochemistry for cleaved caspase-3 and TUNEL. RESULTS: There was no statistically significant difference between groups. CONCLUSION: Cilostazol had no protective effect on the kidney and the skeletal striated muscle in rats submitted to acute ischemia and reperfusion in this model.